Placed Upon the Landscape, Casting Shadows: Jewish Canadian Monuments and Other Forms of Memory - Ravvin, Norman (Canadian Jewish Studies / Études juives canadiennes, 2021)
This essay explores monuments, including the National Holocaust Monument in Ottawa, and gravestones in Jewish cemeteries in Montreal and Vancouver. Alongside these sites it considers how Canadian Jewish literature presents possibilities for Jewish history and language to mark the Canadian landscape though a consideration of Leonard Cohen and Eli Mandel. A discussion of Canadian monuments is relevant in light of recent demonstrations focused on removing statues and monuments from parks and government buildings. The essay contrasts community-inspired projects like Vancouver’s Holocaust memorial with Ottawa’s “National” monument, whose unveiling prompted a discussion about appropriate ways to represent history. Cet essai explore les monuments, y compris le monument national de l’Holocauste à Ottawa, et les pierres tombales des cimetières juifs de Montréal et de Vancouver. Parallèlement à ces sites, il examine comment la littérature juive canadienne, notamment les écrits de Leonard Cohen et Eli Mandel, offre des opportunités pour l’histoire et la langue juives de marquer le paysage canadien. Une discussion sur les monuments canadiens est pertinente à la lumière des récentes manifestations visant à retirer les statues et les monuments des parcs et des édifices gouvernementaux. L’essai met en contraste des projets d’inspiration communautaire comme le mémorial de l’Holocauste de Vancouver et le monument « national » d’Ottawa, dont le dévoilement a suscité une discussion sur les moyens appropriés de représenter l’histoire.